Synergistic delivery of resveratrol and ultrasmall copper-based nanoparticles by aptamer-functionalized ultrasound nanobubbles for the treatment of nonalcoholic fatty liver disease - Guo, Xinmin; Huang, Zhihui; Chen, Jialin; He, Kun; Lin, Jianru; Zhang, Hui; Zeng, Yanying (Frontiers in Physiology, 2022)
Nonalcoholic fatty liver disease (NAFLD) is related to the production of reactive oxygen species (ROS) and oxidative stress, so antioxidant treatment can prevent its further development. Ultrasmall copper-based nanoparticles (CuNPs) have shown multiple enzyme-like activities for scavenging oxygen species, providing a new strategy for the treatment of inflammatory diseases. Resveratrol (Res), a natural polyphenol compound, has attracted much attention due to its ability to inhibit oxidative stress. We therefore aimed to first combine these two agents for the treatment of NAFLD. However, due to the poor water solubility and stability of Res, which is easily metabolized in the intestine, the development of a stable and effective carrier became the key to achieving a synergistic effect. Liver-targeted nanocarriers loaded with bioactive compounds may provide a more effective approach for the treatment of NAFLD. Therefore, we developed a novel ultrasonic nanobubble carrying nucleic acid aptamers with liver targeting properties, which has the advantages of a small molecular weight, no immunogenicity, a low cost of synthesis, and high stability through chemical modification. Res and the ultrasmall CuNPs were specifically delivered to liver tissue to maximize therapeutic efficiency. This study found that the combination of these two components can effectively treat inflammation in NAFLD and suggested that liver-targeted NAFLD-specific aptamer-mediated targeted ultrasound nanobubbles that can simultaneously deliver Res and CuNPs may be a safe and effective new platform for NAFLD and other liver diseases.